(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The Review aims at giving the overview of the Diagnosis, treatment, transmission and past outbreaks of Nipah Virus (Henipavirus). Nipah virus is a Zoonotic virus that was emerged in the year 1990 which caused disease outbreaks in animals and Human beings. It was first emerged in Malaysia and Singapore in 1998-1999 which resulted in large outbreak of encephalitis with high amount of death in people and also respiratory disease in pigs which served as amplifying hosts. The most common symptoms of NiV infection in several species of mammals and also in people, are a severe systemic and often deadly neurologic or respiratory disease. The hosts of NiV are several species of pteropid fruit bats. NiV has previously caused outbreaks in Bangladesh and India nearly annually since 2001, making NiV important transboundary biological threats. NiV animal models have been developed previously which have helped in facilliating an understanding of pathogenesis and guided the successful development of both active to passive Immunization. It has the capacity or ability to infect Human beings directly from natural reservoirs or from other various susceptible animals